Legal Aspects of Land Acquisition for the National Capital City (IKN) of the Nusantara - Rosyid Hermawan, Novriansyah; Novizas Shebubakar, Arina; Sadino, Sadino (Dinasti Research, 2024)
This study aims to analyze the legal aspects of land acquisition in the development of the National Capital City (IKN) of the Nusantara. Referring to Presidential Regulation Number 65 of 2022 concerning Land Acquisition and Land Management in the Capital City of the Nusantara, as well as other related laws and regulations such as Law Number 2 of 2012 concerning Land Acquisition and Law Number 6 of 2023 concerning Job Creation, this study identifies challenges and obstacles in its implementation. Primary data is obtained from official legal documents, while secondary data is collected from scientific literature, legal journals, and international case studies. The results of the study show that although the regulation has provided a strong legal basis, there are significant obstacles such as land ownership disputes, inconsistencies in land certificates, and the assessment of compensation prices that are considered low by the community. In addition, indigenous peoples' communal property rights have not been fully accommodated. Agrarian conflicts between state law and customary law add to the complexity of this problem. This study recommends improving regulations and implementing fairer and more transparent implementation to ensure the success of land acquisition and the protection of the rights of affected communities in the Nusantara IKN development project.